Flowing Forward: Insights on Adolescent Girls’ Menstrual Hygiene and Health - Ahmad Mir, Mashooq; Altaf Dar, Mohd; Qadir, Afshana (American Journal of Biomedicine and Pharmacy, 2024)
During the transition from childhood to adulthood, adolescence represents a period marked by physical, mental, and social changes. Among these changes, menstrual issues frequently arise as a significant concern, leading to frequent visits to healthcare providers for adolescent girls. However, their understanding of reproductive health, including menstruation, often remains incomplete and hindered by sociocultural barriers. In many parts of India, a large proportion of teenage girls lack knowledge about menstruation, reproduction, and sexuality due to persistent taboos and myths surrounding menstruation. Poor personal hygiene practices and unsanitary conditions during menstruation further increase the risk of reproductive tract infections and gynecological problems, particularly in resource-limited settings where access to basic facilities like water, sanitation, and privacy is lacking. Improving housing conditions with essential amenities is crucial in addressing these challenges. Additionally, making affordable sanitary pads accessible to all girls is imperative. Establishing specialized gynecological clinics for teenagers is urgent to provide tailored healthcare services. Sensitization programs and counseling sessions in schools, along with comprehensive education about menarche and menstrual issues, can empower girls to manage their menstrual health better and seek appropriate medical care when needed